1990
DOI: 10.1128/jb.172.7.3758-3771.1990
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial cell shape regulation: testing of additional predictions unique to the two-competing-sites model for peptidoglycan assembly and isolation of conditional rod-shaped mutants from some wild-type cocci

Abstract: The two-competing-sites model for peptidoglycan assembly for bacterial cell shape regulation suggests that in rods, bacterial cell shape depends on the balance between two reactions (sites), one responsible for lateral wall elongation and the other responsible for septum formation. The two reactions compete with each other so that no lateral wall can be formed during septum formation and vice versa. When the site for lateral wall elongation overcomes that for septum formation, long rods or filaments are formed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
85
0

Year Published

1992
1992
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(93 citation statements)
references
References 47 publications
8
85
0
Order By: Relevance
“…MCI23 cells have slower septum closure rates but much faster cell elongation rates compared with wt MC4100 cells, whereas ΔmatP cells exhibit the opposite changes relative to wt BW25113 cells (SI Appendix, Table S3). These anticorrelated effects support a model in which lateral and septal cell wall synthesis may compete for a constant pool of enzymes or PG precursors, the level of which is determined by the growth condition (92,93). The positive correlation between septum closure and elongation rates that we observed for wt cells (Fig.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…MCI23 cells have slower septum closure rates but much faster cell elongation rates compared with wt MC4100 cells, whereas ΔmatP cells exhibit the opposite changes relative to wt BW25113 cells (SI Appendix, Table S3). These anticorrelated effects support a model in which lateral and septal cell wall synthesis may compete for a constant pool of enzymes or PG precursors, the level of which is determined by the growth condition (92,93). The positive correlation between septum closure and elongation rates that we observed for wt cells (Fig.…”
Section: Discussionsupporting
confidence: 68%
“…6 C and D and SI Appendix, Table S3). These results suggest that normal FtsI activity may inhibit lateral cell wall synthesis, which contributes most significantly to cell elongation, and that the competitive balance between lateral and septal cell wall synthesis (92,93), if present, is shifted in the MCI23 mutant.…”
Section: Decreased Activity Of Pg Synthesis Enzyme Ftsi Decreases Septummentioning
confidence: 79%
See 1 more Smart Citation
“…Studies have found 50 nm bundles of peptidoglycan fibers during protoplast regeneration in Bacillus licheniformis (26) and apparent striations on the cell walls of B. subtilis and Lactobacillus helveticus (27,28). Peptidoglycan in B. subtilis is biosynthesized by two sets of machinery; one dedicated primarily to the cylinder to allow cell elongation and the other to the septum for cell division (29). Our cell wall preparations contained well defined septa at all stages of formation ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This layer is a meshwork of disaccharide chains (alternating N-acetylglucosamine and N-acetylmuramic acid sugars) cross-linked by short peptide bridges. Rod-shaped bacteria are believed to possess two peptidoglycan synthesis complexes with distinct activities: one for elongation along the cell length and the other for cell division (1,3,4). It is thought that maintenance of a regular rod shape requires the activities of these two complexes to be carefully balanced (3).…”
mentioning
confidence: 99%